ANALISIS KEPUTUSAN PEMBELIAN MAKANAN KHAS DAERAH DITINJAU DARI PENGARUH WORD OF MOUTH DAN KUALITAS PRODUK SERTA DAMPAKNYA PADA LOYALITAS PELANGGAN - Thalib, Supriadi; Setiarini, Setiarini; Ardianto, Yuli (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose- This study analyzes the effect of word of mouth, product quality on consumer purchasing decisions, and simultaneously analyzes purchasing decisions, word of mouth, and product quality on customer loyalty. Design/methodology/approach- Data were collected from 150 respondents from 3 (three) areas Jakarta, Depok, and Bogor. Data analysis techniques using Path Analysis. Findings- word of mouth and product quality have a positive effect on purchasing decisions, as well as simultaneous purchasing decisions, word of mouth affects customer loyalty but not product quality. Product quality does not affect loyalty consumption of local specialties in the city of Bogor-Depok Implications-Local culinary SMEs are advised to maintain consumer satisfaction by interacting with them to create a positive impression. Consumers who have a positive impression will provide the word of mouth so as to increase purchasing decisions and customer loyaltyKeywords: Word of Mouth, Quality Product, Purchasing Decision, Loyalty